Modeling Turbulent Flow Around a Thin Rectangle Using the K–Ε Turbulence Model in Comsol Multiphysics (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
The article presents the results of numerical simulation of flow around a rectangular airfoil using standard Comsol solvers Multiphysics based on the k–ε turbulent model. Calculations are performed at the Reynolds number 10,000 < Re < 2,000,000 and attack angles α = 0°–20°. The dependences of the velocity distribution, pressure and other flow characteristics on the attack angle are obtained. The constructed model demonstrated good convergence, stability and high accuracy of calculations.